A study on the use of henna plant (Lawsonia inermis Linn) for the treatment of fungal disease (Trichophypton verrucosum) in calves - HIZLI, H. (Journal of the Hellenic Veterinary Medical Society, 2021)
The aim of this study was to investigate the usability of henna plant (Lawsonia inermis Linn) in the treatment of dermatophytosis lesions (Trichophypton verrucosum) in cattle. The animal material of the trial consisted of 50 holstein calves between the ages of 4 and 6 months, who were found to have a dermatophytosis lesion on their face and neck in their clinical examination. The experiment was organized on a three-group repeated measurement trial plan. I. Group: Trichlorfon (Neguvon 75%, Bayer) ointment, II. Group: Henna applied, and III. Group: Control Group, no treatment, and 20 (10 females, 10 males), 20 (10 females, 10 males), and 10 (5 females, 5 males) totally 50 calves used, respectively. The research was continued for 14 days until the lesions were completely healed. I. and II. Groups were observed the best healing in the calves, respectively. In the III. Group without any treatment, there was no improvement and the lesions were enlarged. In addition, the effect of gender in the treatment process of dermatophytosis lesions was insignificant. As a result of this study, it is thought that henna plant can be used in the treatment of dermatophytosis.